Laser-activated irrigation: Cavitation and streaming effects from dental lasers - Clara Isabel Anton y Otero; Laurine Marger; Enrico Di Bella; Enrico Di Bella; Albert Feilzer; Ivo Krejci (Frontiers Media S.A., 2023)
IntroductionThe aim of the present study was to assess the generation of laser-activated irrigation (LAI) with a 9,300-nm CO2 laser, a 455- and 970-nm diode laser, as well as an 810- and 980-nm diode laser with and without carbon-coated "hot tips" for improved irrigation in endodontics. Therefore, the formation of cavitation bubbles at the laser tip ends in different liquids was evaluated and compared with the traditionally applied Er:YAG laser.MethodsThe CO2 laser was applied at different power settings at a repetition rate of 14 Hz, SIROLASE for each wavelength at 10% Duty Cycle, and WISER with both wavelengths at different power settings and wavelengths. The LAI was videotaped with a high-speed camera. To measure the streaming velocity due to cavitation, all lasers were loosely coated with carbon particles and activated in pure water. Then, due to LAI, moving particles were videotaped with the same high-speed camera setup. To determine the streaming velocities, the movement of one carbon particle was tracked with the help of a measuring tool in ImageJP software and streaming velocities were calculated.ResultsWith both diode laser devices at four wavelengths, it was only possible to introduce clear cavitation bubbles with low-power parameters (180 mW for the SIROLASE and 200 mW average power for the WISER laser), with the black coating of the laser tips. The 9,300-nm CO2 laser produced clear cavitation bubbles with all tested parameters. Consequently, all tested lasers produced streaming of the liquid, with decreasing velocities at increasing distances from the laser tip: Er:YAG laser 6.4 m/s, CO2 laser up to 5 m/s, and diode lasers in the range of 0.01-0.09 m/s. LIA with the Er:YAG and 9,300-nm CO2 lasers generated high and similar streaming velocities. The diode lasers tested generated significantly lower streaming velocities.